2010
DOI: 10.1097/moo.0b013e32833e0601
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in hair cell development and deafness

Abstract: Purpose of review-The identification of transcriptional activators and repressors of hair cell fates has recently been augmented by the discovery of microRNAs (miRNAs) that can function as post-transcriptional repressors in sensory hair cells.Recent findings-miRNAs are ~21 nucleotide single-stranded ribonucleic acids that can each repress protein synthesis of many target genes by interacting with messenger RNA transcripts. A triplet of these miRNAs, the miR-183 family, are highly expressed in vertebrate hair c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Similar mutations in the seed region of human miR-96 lead to progressive nonsyndromic deafness. Gain-of-function experiments in zebrafish have shown that increased expression of miR-183 family members can lead to enlarged or duplicated otocysts as well as increased numbers of hair cells (Li and Fekete 2010). The specific genes within the inner ear that are regulated by miR-96 or miR-183 have not been determined yet.…”
Section: Micrornas and Cochlear Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar mutations in the seed region of human miR-96 lead to progressive nonsyndromic deafness. Gain-of-function experiments in zebrafish have shown that increased expression of miR-183 family members can lead to enlarged or duplicated otocysts as well as increased numbers of hair cells (Li and Fekete 2010). The specific genes within the inner ear that are regulated by miR-96 or miR-183 have not been determined yet.…”
Section: Micrornas and Cochlear Developmentmentioning
confidence: 99%
“…MicroRNAs (miRNAs), single-stranded RNAs with a length of approximately 21 nucleotides in their active form, have recently been identified as important regulators of many developmental processes, including the inner ear (Soukup et al 2009;Li and Fekete 2010). miRNAs hybridize with specific RNA sequences in the 3 ′ untranslated regions (UTRs) of different mRNA transcripts, which leads to inhibition of protein synthesis.…”
Section: Micrornas and Cochlear Developmentmentioning
confidence: 99%
“…Point mutations in one member of this family, miR-96, underlie DFNA50 autosomal deafness in humans and lead to abnormal hair cell development and survival in mice. In zebrafish, overexpression of the miR-183 family induces extra and ectopic hair cells, whereas knockdown reduces hair cell numbers [Li and Fekete, 2010]. An aging hair cell struggles to maintain its stereociliary bundle, mechanosensory channels, tip links, ribbon synapses, apical tight junctions and/or all the other specialized components needed for detection and transmission at maximal sensitivity.…”
Section: Micro-rnasmentioning
confidence: 99%
“…This is consistent with our observation that all 4 miRNAs were decreased in the human inner ear of old elderly subjects compared to young elderly subjects. The finding that the expression of certain miRNAs are increased up to 24 months in other organs, but decreased at 9 months or 16 [Friedman and Avraham, 2009;Friedman et al, 2009] Solute carrier family 12 (sodium/potassium/ chloride transporters), member2 (Slc12a2), Claudin (Cldn12) Brain-derived neurotrophic factor (Bdnf) [Friedman et al, 2009] -1.87 miR-18a Cochlear and vestibular hair cells Spiral and vestibular ganglion ganglion > hair cell [Friedman and Avraham, 2009;Friedman et al, 2009] Highly upregulated after stroke Inhibition of miR-18a increased apoptotic cell death Ataxia telangiectasia mutated (ATM) [Song et al, 2011;Wu et al, 2013] 1.12 miR-30b Cochlear and vestibular hair cells Spiral and vestibular ganglion Supporting cells Basilar membrane [Friedman and Avraham, 2009;Friedman et al, 2009] Significantly reduced in response to oxidative stress stimulation, and could inhibit mitochondrial fission and consequent apoptosis [Li et al, 2010] 1.33 miR-96 Cochlear and vestibular hair cells Spiral and vestibular ganglion Inner sulcus Spiral limbus Ganglion < hair cell (embryo) Ganglion > hair cell (after birth) [Weston et al, 2006;Sacheli et al, 2009;(Weston et al, 2011] Mutation of miR-96 responsible for DFNA50 [Mencia et al, 2009 [Friedman and Avraham, 2009;Friedman et al, 2009] Protein kinase B (AKT1) [Jin et al, 2013] -1.57 miR-100 Vestibular ganglion only [Weston et al, 2006] Ataxia telangiectasia mutated (ATM) [Ng et al, 2010] -1.67 miR-124 Spiral and vestibular ganglion Cochlea > vestibula 8-fold higher expression in cochlea [Weston et al, 2006;Elkan-Miller et al, 2011] Downregulates the expression of various neuronal genes and controls CNS development and behavior [Weng et al, 2013] [Wang et al, 2010a, b] Forkhead-box P2 (FOXP2) [Shi et al, 2013] -1.77 143 months in the inner ear, may reflect the earlier appearance of inner ear aging relative to other organs. A recent study revealed the possibility of cochlear hair cell regeneration, not only in avian [Corwin and Cotanche, 1988;Ryals and Rubel, 1988...…”
Section: Mirna Expression Of the Mouse Inner Ear During Agingmentioning
confidence: 99%
“…In the past several years, emerging evidence has linked miRNAs to inner ear biology and pathogenesis. Several excellent reviews on miRNA expression and function in the inner ear have been published [Friedman and Avraham, 2009;Soukup, 2009;Lewis and Steel, 2010;Li and Fekete, 2010;Kopecky and Fritzsch, 2011;Patel and Hu, 2012;Rudnicki and Avraham, 2012;Ushakov et al, 2013]. Current reviews bring to light developments in miRNA research as they pertain to the role of miRNAs in inner ear development, genetic hearing loss, and inner ear homeostasis.…”
Section: Introductionmentioning
confidence: 99%